High-Resolution Structural Analysis of Chromatin at Specific Loci: Saccharomyces cerevisiae Silent Mating Type Locus HMLα - Weiss, Kerstin (American Society for Microbiology, 1998)
Genetic studies have suggested that chromatin structure is involved in repression of the silent mating type loci in Saccharomyces cerevisiae. Chromatin mapping at nucleotide resolution of the transcriptionally silent HMLα and the active MATα shows that unique organized chromatin structure characterizes the silent state of HMLα. Precisely positioned nucleosomes abutting the silencers extend over the α1 and α2 coding regions. The HO endonuclease recognition site, nuclease hypersensitive at MATα, is protected at HMLα. Although two precisely positioned nucleosomes incorporate transcription start sites at HMLα, the promoter region of the α1 and α2 genes is nucleosome free and more nuclease sensitive in the repressed than in the transcribed locus. Mutations in genes essential for HML silencing disrupt the nucleosome array near HML-I but not in the vicinity of HML-E, which is closer to the telomere of chromosome III. At the promoter and the HO site, the structure of HMLα in Sir protein and histone H4 N-terminal deletion mutants is identical to that of the transcriptionally active MATα. The discontinuous chromatin structure of HMLα contrasts with the continuous array of nucleosomes found at repressed a-cell-specific genes and the recombination enhancer. Punctuation at HMLα may be necessary for higher-order structure or karyoskeleton interactions. The unique chromatin architecture of HMLα may relate to the combined requirements of transcriptional repression and recombinational competence.